Factors Associated with COVID-19 Mortality at Setiu District, Terengganu State of Malaysia in 2021 - Ahmad Khan, Erwan Ershad; Ahmad, Mohd Hanief; Mohamed, Kamarul Azhar; Shaari, Muhammad Hanif; Embong, Kasemani (International Journal of Human and Health Sciences (IJHHS), 2022)
Background: COVID-19 infections caused a range of morbidities and mortalities especially in the high-risk group patients. Objective:To determine the factors associated with COVID-19 related mortality in a population of Malaysia.